The Representation of Environmental Awareness in the Indonesian ELT Textbook for Senior High School Students - Andayani T., Made Adi; Laelani Marda, Istivana; Fitriani , Ika (Institut Agama Islam Negeri Palopo, 2025)
The lack of environmental awareness among the general populace was one of the contributing causes of the environmental problem. Schools or other formal educational institutions can be used to increase students’ environmental awareness. English Language Teaching (ELT) textbooks in Indonesia should contain language materials that not only cover the English material but also consist of environmental awareness. However, some ELT textbooks published in Indonesia and abroad still do not sufficiently cover environmental awareness. Therefore, this research analyzed the representation of environmental awareness in the ELT textbook based on the element of environmental awareness by Kokkinen (2013). Furthermore, critical discourse analysis (CDA) was chosen as the research design in this study, and the data analysis method used Fairclough’s 1995 Three-Dimensional Model (Description, Interpretation, Explanation). The result shows that the representation of environmental awareness is found in various forms of visual and textual materials in the textbook. All topics that represent environmental awareness are problems that occur in everyday life, and almost happen to students today. Keywords: Critical Discourse Analysis (CDA), Environmental Awareness, Indonesian ELT Textbook